2005
DOI: 10.1007/s10562-004-3457-2
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic oxidation of methanol to methyl formate over silver ? a new purpose of a traditional catalysis system

Abstract: Catalytic reaction was performed in the unregarded temperature region over silver catalysts with long catalytic lifetime for the conversion of methanol to methyl formate. O a -saturated or O c -saturated silver catalysts were studied individually to identify the roles of O a , O c in the oxidative esterification of methanol over an unsupported polycrystalline silver catalyst. A synergic process is proposed based on the coexistence of a-oxygen species and c-oxygen species on the surface of polycrystalline silve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In a study on methanol oxidation over silver catalysts, the authors reported that the catalytic oxidative reaction of methanol to methyl formate is related to a synergic process concerning oxygen species on the silver surface. The mechanism proposed in this Os-Me system starts with methanol dehydrogenation to form adsorbed formaldehyde and methoxy; thereafter, formaldehyde reacts with adsorbed OH or O to form adsorbed formate, that reacts with methoxy and forms methyl formate [79,90]. Thus, Me formed as a by-product of acetaldehyde decomposition can be the precursor of MeF, with formaldehyde and CH3O as intermediates.…”
Section: Proposed Simplified Mechanism For Acetaldehyde Decompositionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a study on methanol oxidation over silver catalysts, the authors reported that the catalytic oxidative reaction of methanol to methyl formate is related to a synergic process concerning oxygen species on the silver surface. The mechanism proposed in this Os-Me system starts with methanol dehydrogenation to form adsorbed formaldehyde and methoxy; thereafter, formaldehyde reacts with adsorbed OH or O to form adsorbed formate, that reacts with methoxy and forms methyl formate [79,90]. Thus, Me formed as a by-product of acetaldehyde decomposition can be the precursor of MeF, with formaldehyde and CH3O as intermediates.…”
Section: Proposed Simplified Mechanism For Acetaldehyde Decompositionmentioning
confidence: 98%
“…It is worth noting that we have not detected formaldehyde at the exit of the DBD reactor whereas it has been detected on the catalyst surface. There are two reasons for this: formaldehyde is a short-lived species [77] and it is strongly adsorbed onto silver catalyst [79]. selectivity is dependent on the O3:HCHO ratio and the relative humidity (RH).…”
Section: Proposed Simplified Mechanism For Acetaldehyde Decompositionmentioning
confidence: 99%
“…However, it is possible to synthesize methyl formate from partial oxidation of methanol using suitable catalyst without using CO [100]. Monolithic unsupported np-Au has shown promising potential to be used in a gas-phase catalysis for selective conversion of methanol to methyl formate [101].…”
Section: Methanol Oxidationmentioning
confidence: 99%
“…The first one, which is also known as Formox process, uses metal oxides (e.g., vanadium, molybdenum, or iron oxide) and is operated in the temperature region of 270–400 °C. The other one, which is also used at the investigated production plants of this study, is based on silver crystals and operated at significantly higher temperatures (600–720 °C) [27–30]. The formation of FA can be written as follows: …”
Section: Production Of Formaldehydementioning
confidence: 99%